Completion of the Human Papillomavirus Vaccination Series Among Adolescent Users and Nonusers of School-Based Health Centers. (September 2019) - Munn, Meaghan S.; Kay, Meagan; Page, Libby C.; Duchin, Jeffrey S.
Objectives: Uptake and completion of the human papillomavirus (HPV) vaccine series among adolescents are suboptimal in the United States. We examined immunization registry data to determine completion of the 3-dose HPV vaccine series among adolescents in Seattle, Washington, born during 1995-2000 who received ≥1 dose of HPV vaccine. Methods: Immunization data included the administrating facility, which identified adolescents who used school-based health centers (SBHCs) for any HPV vaccine dose. We calculated completion of the 3-dose series at any time and on time by the 13th birthday. We stratified analyses by sex and assessed differences in on-time and any-time completion between users and nonusers of SBHCs. Results: Overall, 67.9% (8612 of 12 676) of females and 41.8% (3560 of 8521) of males with ≥1 dose of HPV vaccine completed the 3-dose series. Compared with female SBHC nonusers, female SBHC users had 37% higher odds of completing the series at any time (adjusted odds ratio [aOR] = 1.37; 95% CI, 1.19-1.58) and 33% higher odds of completing the series on time (aOR = 1.33; 95% CI, 1.08-1.64). Compared with male SBHC nonusers, male SBHC users had 45% higher odds of completing the series at any time (aOR = 1.45; 95% CI, 1.23-1.70) and 79% higher odds of completing the series on time (aOR = 1.79; 95% CI, 1.11-2.89). Conclusion: Adolescent SBHC users had higher odds of completing the HPV vaccine series than adolescents who received all doses in traditional health care settings. SBHCs should be leveraged to increase adolescent immunization rates.